Stressed Mothers Receiving Infant Mental Health-Based Early Head Start Increase in Mind-Mindedness - Brophy-Herb, Holly E.; Choi, Hailey Hyunjin; Senehi, Neda; Martoccio, Tiffany L.; Bocknek, Erika London; Babinski, Michal; Krafchak, Stephen; Accorsi, Courtney; Azmoudeh, Roxanna; Schiffman, Rachel (Frontiers in Psychology, 2022)
Maternal mind-mindedness is a characteristic of supportive parenting and contributes to many positive social-emotional outcomes in early childhood. However, there is limited knowledge of mind-mindedness among parents experiencing parenting stress from low-income settings. This is a critical gap in evidence given the robust role of supportive parenting in children’s development and the capacity of home-based interventions to improve children’s outcomes through enhancing supportive parenting. This study examined: 1) maternal mind-mindedness, operationalized as mothers’ appropriate mind-related comments (MRC), across toddlerhood in mothers of toddlers who participated in infant mental health (IMH) based Early Head Start (EHS) services; and 2) whether parenting stress moderated EHS program effects on appropriate MRC over time. Data from a primarily White midwestern site in the U.S. were collected at study enrollment and when toddlers were 14-, 24-, and 36-months of age (N = 152; mothers Mage = 22.4 years, SD = 5.1; toddlers Mage = 14.4 months, SD = 1.3; 51% females). Data included parent-completed questionnaires and observed parent-child interactions, which were coded for MRC. Although there were no main effects of EHS programming on mothers’ appropriate MRC over time, multilevel growth curve modeling indicated that parenting stress moderated EHS effects on mothers’ appropriate MRC over time. Among mothers with greater parenting stress, those who received IMH-based EHS services demonstrated greater proportions of MRC over time than did mothers with greater stress in the control group. IMH-based parenting interventions that target parenting stress may promote appropriate MRC in low-income populations during toddlerhood.